A salivary ferritin in the whitefly suppresses plant defenses and facilitates host exploitation. (5th April 2019) - Su, Qi; Peng, Zhengke; Tong, Hong; Xie, Wen; Wang, Shaoli; Wu, Qingjun; Zhang, Jianmin; Li, Chuanren; Zhang, Youjun
Abstract : A secreted ferritin in the whitefly Bemisia tabaci enables insect feeding and suppresses plant immune responses by disruption of H2 O2 accumulation and JA signaling. Abstract: The whitefly Bemisia tabaci is an important pest of worldwide agriculture. Previous work has shown that B. tabaci actively suppresses host plant defenses, but our knowledge of the specific mechanisms involved remains limited. Here we describe a B. tabaci salivary protein, the ferritin BtFer1, and its role in facilitating exploitation of host plants. We show that BtFer1 exhibits Fe 2+ binding ability and ferroxidase activity, and that secretion of BtFer1 during B. tabaci feeding suppresses H2 O2 -generated oxidative signals in tomato ( Solanum lycopersicum ). Silencing BtFer1 enhanced the induction of the jasmonic acid (JA)-mediated defense signaling pathway in response to whitefly feeding, and led to increased callose deposition and the production of proteinase inhibitors that prevent whiteflies from continuously ingesting and digesting phloem sap. Consistent with these effects, silencing BtFer1 reduced whitefly survival on tomato but not on artificial diet. Using a JA-deficient spr2 mutant plant further showed that suppression of JA defenses by BtFer1 is sufficient to increase B. tabaci survival. Taken together, these results demonstrate that BtFer1 acts as an effector protein that mediates whitefly–tomato interactions. These findings represent an important step forward in understanding the molecular mechanisms by which whiteflies and other insect herbivores suppress host plant defenses.